Bomspotting : schrijvers en dichters voor vrede - Holvoet-Hanssen, Peter; Barnard, Benno; de Bel, Marc (Berchem: Forum voor Vredesactie; EPO, 2000)
"Peter Holvoet-Hanssen, Benno Barnard, Marc de Bel, Stefan Brijs, Pjeroo Roobjee, Geert van Istendael et al."